Under the Hood. - LIBBY, BRIAN (Architect, 2012)
The article offers the insights of four software designers regarding the updates which enable them to own their software. Among the designers include Marc Syp of Ohio State University who discusses the Grasshopper software, Robert Petty of ZGF Architects who features the update to the Rhinoceros software, and Arne Henneberg of Cooper, Robertson & Partners who discusses Ray for SketchUp software.